GENERAL INFORMATION ABOUT THE SYSTEM OF LEXICAL CONCEPTS AND ITS STUDY (World Bulletin of Social Sciences, 2023)
The word is the main unit of language that conveys meaning. Words and word combinations indicate specific objects, abstract concepts, emotions. The sum of all the words and phrases in the language is called vocabulary or lexicon. Lexicology is a department that studies the composition of the Uzbek language. Lexicology studies the characteristics of the words in the dictionary, the expression of meaning in speech, the activity of use, enrichment, the obsolescence of some words, the phenomenon of meaning migration. Therefore, lexicology is the linguistic basis of the methodology of working on the dictionary